2017
DOI: 10.1016/j.jpain.2016.12.008
|View full text |Cite
|
Sign up to set email alerts
|

A Local Inflammatory Renin-Angiotensin System Drives Sensory Axon Sprouting in Provoked Vestibulodynia

Abstract: Vestibulodynia is a form of provoked vulvodynia characterized by profound tenderness, hyperinnervation, and frequently inflammation within well-defined areas of the human vestibule. Prior experiments in animal models show that inflammatory hypersensitivity and hyperinnervation occur in concert with establishment of a local renin-angiotensin system (RAS). Moreover, mechanical hypersensitivity and sensory axon sprouting are prevented by blocking effects of angiotensin II on AT2 receptors. This case-control study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(56 citation statements)
references
References 54 publications
(87 reference statements)
3
53
0
Order By: Relevance
“…However, hindpaw Ang II injection led to local M⌽ infiltration in the skin without any influence on microglia/M⌽s in the DRG and spinal cord. Increased peripheral M⌽ infiltration and expression of renin-angiotensin system (RAS) components therein, such as angiotensinogen, renin, angiotensin-converting enzyme, and AT2R, have been shown in rodent models of CFA-induced inflammation and vestibulodynia (Chakrabarty et al, 2013(Chakrabarty et al, , 2018Liao et al, 2017). Furthermore, increased expression of RAS components, including AT2R, has been shown to accompany the differentiation of M⌽s from monocytes (Okamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, hindpaw Ang II injection led to local M⌽ infiltration in the skin without any influence on microglia/M⌽s in the DRG and spinal cord. Increased peripheral M⌽ infiltration and expression of renin-angiotensin system (RAS) components therein, such as angiotensinogen, renin, angiotensin-converting enzyme, and AT2R, have been shown in rodent models of CFA-induced inflammation and vestibulodynia (Chakrabarty et al, 2013(Chakrabarty et al, , 2018Liao et al, 2017). Furthermore, increased expression of RAS components, including AT2R, has been shown to accompany the differentiation of M⌽s from monocytes (Okamura et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…A recent phase II clinical trial of a peripherally acting AT2R antagonist demonstrated successful alleviation of neuropathic pain associated with PHN (Rice et al, 2014). However, the underlying mechanism remains enigmatic, with a number of studies showing that the mechanism of action may involve AT2R antagonism directly on sensory neurons (for review, see and other studies finding no direct functional role of sensory neuron AT2R (Forte et al, 2016;Liao et al, 2017;Chakrabarty et al, 2018). We began with an unambiguous verification of the role of Ang II signaling in pain sensitization.…”
Section: Ang II Induces Peripheral Mechanical Pain Hypersensitivity Amentioning
confidence: 99%
See 1 more Smart Citation
“…Neurochemical characterization of nerve fibres in vaginal biopsies from women with vulvodynia is limited. Increased CGRP-containing nerve fibres (Bohm-Starke et al, 1999) and fibres expressing TRPV1 (Tympanidis et al, 2004) and TRPV4 (Liao et al, 2017) have been identified. TRPV1 receptors are activated by multiple mechanical and chemical stimuli and are mainly found in nociceptors, including many DRG neurons containing both SP and CGRP (Price and Flores, 2007).…”
Section: Infiltration Of Immune-competent Cells Is a Hallmark Of Inflmentioning
confidence: 99%
“…Ang(1-7) in turn may stimulate the Mas receptor (MasR), exerting anti-inflammatory and regenerative effects [8][9][10]. Importantly, in addition to the systemic RAS, several local RAS have been also identified in individual organs, where it plays a role not only in the homeostasis of blood pressure but also in the regulation of local immune response [11][12][13][14].…”
mentioning
confidence: 99%